Value chain analysis of vegetables (onion, tomato, potato) in Ethiopia: A review - Desalegn Wondim (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Even though different studies were takes place, none of them can address the effective production constraints, marketing and its constraints and gender issues of vegetables as vegetables are one highly perishable agricultural products. Therefore, the reviewer wants to assess the production status and its constraints, marketing condition and value chain actors including the gender aspects helps for policy makers to prepare intervention policies which helps to develop its contribution from the agricultural sector .From production perspective low yield, due to lack of production and marketing skill, lack of capital, Adulteration (poor quality of seed) are found to be the constraints of production and productivity. Through the identification of value chain actors the commonly involved actors found to be producers, the middlemen/brokers, traders and consumers along with supporters and influencers. In marketing of vegetables ,mall holders in rural areas are often poorly linked to markets and do not adequately access functional market information. Often middlemen do make much higher marketing margins than the producers, limiting the motivation of farmers to expand vegetable production, lack of storage facilities as vegetables are highly perishable product affects marketability of the product. And finally gender issue is one of an important area which is not addressed in vegetable production and marketing (value chain) and thus future researchers should take compressive (value chain) approaches to address multi Sectoral constraints of vegetables in production and marketing.